2014
DOI: 10.1158/0008-5472.can-14-0037-t
|View full text |Cite
|
Sign up to set email alerts
|

CD47 in the Tumor Microenvironment Limits Cooperation between Antitumor T-cell Immunity and Radiotherapy

Abstract: While significant advances in radiotherapy have increased its effectiveness in many cancer settings, general strategies to widen the therapeutic window between normal tissue toxicity and malignant tumor destruction would still offer great value. CD47 blockade has been found to confer radioprotection to normal tissues while enhancing tumor radiosensitivity. Here we report that CD47 blockade directly enhances tumor immunosurveillance by CD8+ T cells. Combining CD47 blockade with irradiation did not affect fibros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
161
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 52 publications
(64 reference statements)
7
161
0
Order By: Relevance
“…Meanwhile, new data from the phase I trial of TTI-621 (a SIRPaFc fusion protein) suggest that repeat dosing of TTI-621 overcame the antigen sink while maintaining clinically acceptable platelet levels (33), which could be an effective strategy to circumvent antigenic sinks in other studies. Although many studies have revealed that the therapeutic benefit of blocking CD47-SIRPa interactions in immune competent hosts depends on the myeloid immune subsets, including neutrophils, NK cells, T cells, and dendritic cells (34)(35)(36), the primary cell type contributing to effectiveness is macrophages (10,(37)(38)(39). Our data here also showed that targeting CD47 by SIRPaD1-Fc elicited potent macrophage-mediated antitumor efficacy in NSCLC.…”
Section: Discussionsupporting
confidence: 61%
“…Meanwhile, new data from the phase I trial of TTI-621 (a SIRPaFc fusion protein) suggest that repeat dosing of TTI-621 overcame the antigen sink while maintaining clinically acceptable platelet levels (33), which could be an effective strategy to circumvent antigenic sinks in other studies. Although many studies have revealed that the therapeutic benefit of blocking CD47-SIRPa interactions in immune competent hosts depends on the myeloid immune subsets, including neutrophils, NK cells, T cells, and dendritic cells (34)(35)(36), the primary cell type contributing to effectiveness is macrophages (10,(37)(38)(39). Our data here also showed that targeting CD47 by SIRPaD1-Fc elicited potent macrophage-mediated antitumor efficacy in NSCLC.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, depletion of either of these cell types resulted in marked attenuation of the antitumor effect of MY-1, implicating these immune cells in this effect. It has recently been demonstrated that the efficacy of CD47 blockage against tumors required adaptive immune responses in immunocompetent mouse tumor models (48)(49)(50). The inhibition of the CD47-SIRPα interaction by SIRPα or CD47 blockage is thus probably important for enhancing T cell-mediated destruction of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The radioresistance of cd47-null cells or blockade of CD47 in WT cells requires induction of protective autophagy (22). Moreover, studies in tumor-bearing mice revealed that, although normal tissues and tumor associated CD8 ϩ T cells in these mice are protected from radiation injury, irradiated tumors show increased CD8 ϩ T cell-dependent therapeutic ablation after CD47 blockade (20,23). Thus, the CD47 pathway is a promising therapeutic target to enhance the efficacy of tumor irradiation while minimizing damage of critical organs exposed to the radiation field.…”
mentioning
confidence: 99%